Association of HOTAIR Polymorphisms with Susceptibility to Psoriasis in a Chinese Han Population. (4th August 2021) - Yao, Xinyu; Hao, Siyu; Xue, Tiankuo; Zhou, Keren; Zhang, Yu; Li, Hang
Abstract : Psoriasis is a common disease in dermatology, but its etiology and pathogenesis have not been fully elucidated. In recent years, researchers have found that HOX transcript antisense RNA (HOTAIR) plays an important role in biological processes as an important long-chain noncoding RNA (lncRNA). The goal of this study was to investigate the association between HOTAIR polymorphisms and psoriasis in a Chinese Han population by screening key candidate single-nucleotide polymorphism (SNPs) sites in HOTAIR. A total of 269 patients diagnosed with psoriasis and 273 healthy control subjects were enrolled in this case-control study. Three SNPs of HOTAIR were genotyped: SNP1 (rs12826786), SNP2 (rs1899663), and SNP3 (rs4759314). All polymorphisms were in Hardy-Weinberg equilibrium in both the control and patient groups, and the SNPs were in linkage disequilibrium. The distribution of the rs4759314 genotype in the control group and case group was statistically significant according to all the models except the recessive model (adjusted p value < 0.05), and the CCG haplotype group had a significant difference (OR   95 % CI = 2.907   1.344 − 6.289, adjusted p value = 0.0263). rs12826786 was associated with a risk of psoriasis according to the dominant model (C/T-T/T vs. C/C: OR   95 % CI = 0.70   0.48 − 1.01, adjusted p value = 0.049) and overdominant model (C/T vs. C/C-T/T: OR   95 % CI = 0.69   0.47 − 1.01, adjusted p value = 0.048). The current work showed that a genomic variant within HOTAIR was associated with a risk of psoriasis, and the clinical value of this study should be further evaluated in the future.